PENGARUH GENDER DAN JENIS PRODUK TERHADAP RESPON KONSUMEN MELALUI PUBLISITAS DAN IKLAN - M. Ismail Alif (Universitas Bina Sarana Informatika, 2017)
The purpose of the research is to prove the long convention among public relations practitioners that publicity message is more superior compare to advertising message. Although publicity have more credible because its third party endorsement empirical finding could not significantly prove the above proposition yet.This experimental study researches some factors – gender and product category – that could prove that publicity have significant different respond to consume. Through pilot studies to get the category product of durable and consumer goods, this experimental study employs 2 marketing message (publicity, advertising) x 2 gender (male, female) x 2 product category (durable, consumer) between subject design.Using One Way Analysis of Variance (ANOVA) the result of this research confirmed that gender is significantly affect consumer exposing to publicity and advertising. Female consumer is more favor to publicity compared to the male consumer who favored advertising. Product category also show affect the consumer perception that they will more keen to see the publicity especially for durable product.